Estimating the Impact of Biodiversity Loss in a Marine Antarctic Food Web - Salinas, Vanesa Anabella (2024)
The consequences of climate change and anthropogenic stressors, such as habitat loss and overexploitation, are threatening the subsistence of species and communities across the planet. Therefore, it is crucial that we analyze the impact of environmental perturbations on the diversity, structure and function of ecosystems. In this study, in silico simulations of biodiversity loss were carried out on the marine food web of Caleta Potter (25 de Mayo/King George Island, Antarctica), where global warming has caused critical changes in the abundance and distribution of benthic and pelagic communities over the last 30 years. We performed species removal, considering their degree and trophic level, and including four different thresholds on the occurrence of secondary extinctions. We examined the impact of extinctions on connectance, modularity and stability of the food web. We found different responses for these properties depending on the extinction criteria used, e.g., large increase in modularity and rapid decrease in stability when the most connected and relatively high-trophic-level species were removed. Additionally, we studied the complexity–stability relationship of the food web, and found two regimes: (1) high sensitivity to small perturbations, suggesting that Potter Cove would be locally unstable, and (2) high persistence to long-range perturbations, suggesting global stability of this ecosystem.